2012
DOI: 10.1111/j.1601-5037.2012.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of periodontal health in patients with schizophrenia and taking antipsychotic medication

Abstract: The researcher concluded that there is a high risk of periodontal disease among patients with schizophrenia, and there is an even higher risk of periodontal disease induced by medication that increased SFR. Preventive dental protocol should be increased during the dental health care of this disadvantaged patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 32 publications
(49 reference statements)
0
40
1
1
Order By: Relevance
“…Only 8.3% did not show any sign of periodontal disease. Another study carried out by Eltas et al (11), after performing a study with 53 psychiatric patients, with a medication which side effect was xerostomy or sialorrhea, concluded that there is a high risk for the development of periodontal disease in schizophrenic patients, and that such risk is even higher in patients that take a medication that causes a decrease in the flow of saliva. In terms of cavity indexes, 56.92% of the sample showed cavities, and 43.08% did not have any lesions of this kind.…”
Section: Discussionmentioning
confidence: 99%
“…Only 8.3% did not show any sign of periodontal disease. Another study carried out by Eltas et al (11), after performing a study with 53 psychiatric patients, with a medication which side effect was xerostomy or sialorrhea, concluded that there is a high risk for the development of periodontal disease in schizophrenic patients, and that such risk is even higher in patients that take a medication that causes a decrease in the flow of saliva. In terms of cavity indexes, 56.92% of the sample showed cavities, and 43.08% did not have any lesions of this kind.…”
Section: Discussionmentioning
confidence: 99%
“…4,25,38,[40][41][42] Evidence suggests various reasons for this including stigma, feelings of shame, helplessness and low self-esteem; 20,43 lack of income and health insurance; 1,20,21 dental fear, anxiety and phobia; [42][43][44][45] and restlessness in the dental waiting environment. 32,46 Mistrust towards dental health providers was an issue identified in the published work that was compounded by negative and unsatisfactory prior encounters with dental professionals and health care providers, 20,32,43 poor communication with oral health providers, 8,20,32,47,48 and PMD's confusion and 59 Clark (2009), 60 Nielsen et al (2011), 61 Arnaiz (2011), 26 Lewis et al (2001), 53 Friedlander and Liberman (1991), 31 Tani (2012), 62 Eltas et al (2013), 63 Shetty (2014), 64 Tang 201465 Lower executive cognitive function and lower awareness of oral health problems Neilsen (2011), 61 Friedlander and Mander (2002), 66 Janardhanan (2011) 67 Loss of self-interest and/or self-esteem Friedlander and Liberman (1991), 31 Griffins et al 2000, 37 Thomas et al (1996) 68…”
Section: Individual Level Influencesmentioning
confidence: 99%
“…Friedlander and Libermann(1991), 31 Friedlander and Mander (2002), 66 Tani (2012), 62 Neilsen (2011), 61 Janardhanan (2011), 67 Eltas et al (2013), 63 Arnaiz (2011), 26 Tang (2014) 65 Medication resulting in xerostomia, plaque index, increased DFMT, oral infection, feelings of thirst Eltas et al (2013), 63 Friedlander and Liberman (1991), 31 Friedlander and Mander (2002), 66 Kirkpatrick (2007), 69 Arnaiz (2011), 26 Neilsen (2011), 61 Increased caries with duration of schizophrenia medication Thomas et al (1996), 68 Angelillo (1995), 38 Eltas et al…”
Section: Smoking And/or Substance Abusementioning
confidence: 99%
“…For example, a recent review showed that stress and trauma (first and second hits), nutritional factors and vitamin D may play a role in schizophrenia [239]. The strong associations among schizophrenia and smoking [240], obesity [241], some atopic disorders [242], sleep disorders [243] and poor periodontal and oral health [244,245] may further contribute to the inflammatory burden in schizophrenia patients. Other factors, however, may be more specific to mood disorders than to schizophrenia.…”
Section: Introductionmentioning
confidence: 99%